Assembling an infrastructure for historic climate data recovery: data friction in practice. Issue 4 (18th June 2019) - Bates, Jo; Goodale, Paula; Lin, Yuwei; Andrews, Penny
Abstract : Purpose: The purpose of this paper is to adopt an assemblage theory lens to examine the socio-material forces shaping the development of an infrastructure for the recovery of archived historical marine weather records for use in contemporary climate data sets. Design/methodology/approach: The authors adopted a data journeys approach to research design, conducting in-depth semi-structured interviews with climate scientists, citizen scientists and a climate historian who were engaged at key sites across the journey of data from historical record to the International Comprehensive Ocean-Atmosphere Data Set database. Interview data were complemented by further qualitative data collected via observations of working practices, a digital ethnography of citizen scientists' online forums, and documentation relevant to the circulation and governance of climate data across emergent data infrastructures. Data were thematically analysed (Ryan and Bernard, 2003 ), with themes being informed primarily by the theoretical framework. Findings: The authors identify and critically examine key points of friction in the constitution of the data recovery infrastructure and the circulation of data through it, and identify the reflexive and adaptive nature of the beliefs and practices fostered by influential actors within the assemblage in order to progress efforts to build an infrastructure despite significant challenges. The authors conclude by addressing possible limitations of some of these adaptive practices within the context of the early twenty-first century neoliberal state, and in light of current debates about data justice. Originality/value: The paper draws upon original empirical data and a novel theoretical framework that draws together Deleuze and Guattari's assemblage theory with key concepts from the field of critical data studies (data journeys, data friction and data assemblage) to illuminate the socio-material constitution of the data recovery infrastructure within the context of the early twenty-first century neoliberal state.